Manipulation of boolean functions based on decision diagrams - Sim, Poh Ching (Universiti Malaysia Sarawak, UNIMAS, 2003)
This thesis provides a brief history of digital system design, an overview of the Boolean functions, an analysis of the trends in representation and manipulation techniques and a technical report on the developed software packages. In addition, it describes a method of defining, analyzing and implementing the Boolean function by decision diagram.